Upaya Meningkatkan Motivasi Belajar Matematika Melalui Penerapan Model Pembelajaran Kooperetif Tipe Team Assisted Individualization - Diana Putri Utami; Melly Andriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This research aimed to improve student learning motivation by implementing of Team Assisted Individualization type of cooperative learning model in increasing student learning motivation on Mathematics subject at the fourth grade of integrated Islamic Elementery School of Darul Hikmah Pekanbaru. It was instigated by the low of students learning motivation. They were: student did not attantion to the teacher explain the material, not ask or not answer the teacher questions, not working on assegnmrnt from the teacher, in and out during the learning process. It was a Classroom Action Reseasch. Subject of this research were a teacher subject and twenty-five students. It was administrated for two meetings and every meeting comprised two meetings. Observation and documentation were the technique of collecting the data. The technique of data analysis were used descriptive analysis with presentage. Based on the data analysis showed that implamentation of Team Assisted Individualization type of cooperative learning model could increase student learning motivation. It could be known before the action, the percentage of students learning motivation was 40.57% ot it was on “low” category. After the action in the first cycle, the persentage increasing to 61.14 or it was on “high” category. In the second cycle, indicators determined. Therefore, it could be concluded that the implamentation of Team Assisted Individualization type of cooperative learning model could increase student learning motivation.